EXTERNAL ENVIRONMENTAL AND ECONOMIC EFFECTS AND THEIR IMPACT ON ECONOMIC DEVELOPMENT - Z. T. Bzishvili (Дискурс)
Characteristic of external effects and their classification are presented. The influence of external effects on the economy of the country is considered. Measures to reduce the negative impact of environmental-economic effects on indicators of economic development of the country are proposed.